A New Generalized Continuity by Using Generalized-Closure Operator - Purushottam Jha; Manisha Shrivastava (International Journal of Mathematics And its Applications, 2018)
We introduce a new class of generalized closed sets namely, $_{N}D_{β}$--closed sets, which is weaker than g--closed(generalized--closed) \cite{lev70}, $semi^{*}$--closed sets \cite{rob12}, $pre^{*}$--closed sets \cite{sel12} and $D_{α}$--closed sets \cite{say16} in topological spaces. Moreover, we introduce $_{N}D_{β}$--continuous and $_{N}D_{β}$--irresolute functions and study its fundamental properties.